Preparation method and application of ruthenium-based synthetic ammonia catalyst promoted by sodium fluoride

By adding sodium fluoride as an additive to the ruthenium-based catalyst, the problems of low activity at low temperature and low pressure and easy deliquescence of the additive were solved, realizing a highly efficient ammonia synthesis reaction. This is suitable for combining renewable energy hydrogen production with ammonia synthesis processes, reducing energy consumption and carbon emissions.

CN120920031APending Publication Date: 2025-11-11TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410583154.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-11
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Traditional ammonia synthesis processes are energy-intensive and have high carbon emissions. Existing ruthenium-based catalysts have low activity at low temperatures and pressures, and their precursors are prone to deliquescence, making them difficult to match with renewable energy hydrogen production processes.

Method used

Sodium fluoride was used as an additive and added to the ruthenium-based catalyst via an aqueous impregnation method to form a sodium fluoride-promoted Ru/MgO catalyst. The stability and promoting effect of sodium fluoride were utilized to enhance the catalyst activity.

Benefits of technology

The catalyst activity is increased 10 times under low temperature and low pressure, and it remains highly stable. It is suitable for coupling renewable energy hydrogen production and ammonia synthesis processes, reducing costs and conforming to the concept of circular economy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120920031A_ABST
    Figure CN120920031A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of catalyst preparation, and provides a preparation method and application of a sodium fluoride promoted ruthenium-based synthetic ammonia catalyst. And uniformly mixing a sodium fluoride solution and the ruthenium precursor / magnesium oxide composite material according to the molar ratio of sodium fluoride to ruthenium of 1: 1-2: 1, stirring and dipping at 50-70 DEG C for 10-15 hours, evaporating the liquid to dryness, drying at 80-100 DEG C for 12-24 hours, and finally calcining the dried product at 350-450 DEG C in a reducing atmosphere for 2-4 hours to obtain the Ru / MgO catalyst promoted by sodium fluoride. According to the method provided by the invention, a trace amount of sodium fluoride additive is added into the Ru / MgO catalyst by using an aqueous phase impregnation method, so that the reaction activity of the Ru / MgO catalyst is improved by 10 times to 2050 micromoles g <-1 > h <-1 > under the conditions that the temperature is 400 DEG C, the pressure is 0.1 MPa and the air speed is 36000 mL g <-1 > h <-1 >, and the Ru / MgO catalyst keeps high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst material preparation, specifically relating to a method for preparing and applying a sodium fluoride-promoted ruthenium-based ammonia synthesis catalyst. Background Technology

[0002] Ammonia (NH3) is one of the world's most widely produced chemicals and a mainstay of the fertilizer industry. Recently, it has received increasing attention as a hydrogen storage carrier due to its high volumetric energy density and ease of storage and transportation, and is considered an ideal energy carrier and carbon-free fuel for the future hydrogen economy. However, traditional ammonia synthesis processes rely on coal and natural gas to produce hydrogen, resulting in significant carbon dioxide emissions. Furthermore, the Haber-Bosch process, based on iron-based catalysts, dominates the ammonia synthesis industry, but its demanding reaction conditions (400–600°C, 20–40 MPa) lead to enormous energy consumption. The ammonia synthesis industry consumes 1–2% of global energy use annually and emits 500 million tons of carbon dioxide.

[0003] With the growing demand for a carbon-free society, a new form of energy utilization has emerged: using renewable energy to electrolyze water to produce hydrogen and coupling it with the ammonia synthesis process to achieve efficient utilization of renewable energy. However, the hydrogen outlet pressure of current water electrolysis equipment is mostly below 3.0 MPa, and the temperature of the dehydrated and deoxygenated hydrogen is about 400°C, which cannot meet the high-temperature and high-pressure requirements of the catalysts used in traditional ammonia synthesis processes. Therefore, there is an urgent need to develop catalysts with high activity under low-temperature and low-pressure conditions.

[0004] Researchers have demonstrated that ruthenium-based catalysts inherently exhibit superior ammonia synthesis activity compared to other transition metal-based catalysts. However, ruthenium-based ammonia synthesis catalysts without additives exhibit very low activity at low temperatures and pressures; for example, Ru / MgO shows an activity of only 200 μmol g / L at 400 °C and 0.1 MPa. -1 h -1 The reason is that nitrogen has a very high N≡N bond energy, often requiring the addition of alkali or alkaline earth metals such as Cs, K, and Ba as electron promoters to facilitate the dissociation of nitrogen by Ru. However, the precursors of these metal elements are usually nitrates, which are highly hygroscopic, potentially leading to catalyst failure during preparation. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and develop a sodium fluoride-promoted ruthenium-based ammonia synthesis catalyst, overcoming the problem of hygroscopicity of the precursor. Sodium fluoride has a significant effect on improving catalyst activity, and it is inexpensive, readily available, and widely sourced, with a simple addition method, which is beneficial for industrial application. This invention also provides the application of the above catalyst in the field of thermocatalytic ammonia synthesis.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] The first aspect of the present invention is to provide a method for preparing a sodium fluoride-promoted ruthenium-based ammonia synthesis catalyst, comprising the following steps: mixing a sodium fluoride solution and a ruthenium precursor / magnesium oxide composite material uniformly, wherein the molar ratio of sodium fluoride to ruthenium is 1:1 to 2:1, stirring and impregnating at 50 to 70°C for 10 to 15 hours, evaporating the liquid to dryness, drying at 80 to 100°C for 12 to 24 hours, and finally calcining the dried product at 350 to 450°C for 2 to 4 hours under a reducing atmosphere to obtain a sodium fluoride-promoted Ru / MgO catalyst.

[0008] Sodium (Na) is located in the third period of the periodic table. Due to its relatively early position, it is generally considered to have little or no electron-donating ability. Sodium fluoride (NaF) is an ionic compound, a colorless crystal or white solid at room temperature, and does not readily deliquesce. Currently, sodium fluoride is typically a byproduct of phosphate fertilizer production, with the fluorine derived from hydrofluoric acid produced during the processing of fluorinated phosphate rock, thus representing waste utilization. Adding sodium fluoride as an additive to ruthenium-based ammonia synthesis catalysts can significantly improve their performance, greatly reducing catalyst costs and aligning with the principles of a circular economy.

[0009] Further, the preparation method of the ruthenium precursor / magnesium oxide composite material is as follows: an aqueous solution of the ruthenium precursor is added dropwise to deionized water containing magnesium oxide and sodium hydroxide, and a hydrothermal reaction is carried out at 150-170°C for 22-26 hours. After centrifugation, washing, and drying at 80-100°C for 12-24 hours, a solid product is obtained. This solid product is then calcined in air at 400-600°C for 2-4 hours to obtain the ruthenium precursor / magnesium oxide composite material. Preferably, the heating temperature of the forced-air drying oven used for the hydrothermal reaction is 160°C, and the heating time is 24 hours. Preferably, a high-speed centrifuge is used for centrifugation, with the rotation speed set to 10000 r·min. -1 The washing time was 1 minute. The washing method involved adding deionized water, stirring thoroughly, centrifuging, collecting the solid product, and repeating this process 2-3 times. The centrifuge speed was set to 10000 rpm. -1 The time is 1 minute. Preferably, the product is calcined in air using a tube furnace or muffle furnace at a temperature of 500°C and a heating rate of 2°C / min. -1 The time is set to 3 hours.

[0010] Furthermore, the ruthenium precursor is ruthenium trichloride, ruthenium nitrite, or ruthenium acetate.

[0011] Furthermore, the molar ratio of ruthenium precursor to magnesium oxide to sodium hydroxide is 0.34–0.40:17–20:1–1.1.

[0012] Furthermore, the sodium fluoride solution is an aqueous solution of sodium fluoride with a mass percentage of 0.08–0.18 wt%.

[0013] Further, the evaporation time is 10-15 hours. Preferably, the liquid is evaporated for 12 hours after stirring and soaking at 60°C.

[0014] Further, the reducing atmosphere is hydrogen, or a nitrogen-hydrogen mixture, wherein the volume ratio of N2 to H2 is 1:3, or a hydrogen-argon mixture. The temperature of the tube furnace or muffle furnace is set to 400℃, the reduction time is 2-4 hours, and the heating rate is 2℃·min. -1 .

[0015] A second aspect of the present invention is to provide a sodium fluoride-promoted ruthenium-based ammonia synthesis catalyst obtained by the above-described preparation method.

[0016] A third aspect of the present invention is to provide the application of the above-described catalyst in the field of thermocatalytic ammonia synthesis.

[0017] The beneficial effects of this invention are as follows:

[0018] 1) This invention uses an aqueous impregnation method to add a trace amount of sodium fluoride as a promoter to the Ru / MgO catalyst, thereby enabling it to withstand conditions at 400℃, 0.1MPa, and 36000mL g. -1 h -1 The reactivity at space velocity increases 10-fold to 2050 μmol g. -1 h -1 Furthermore, it remains highly stable. Compositional and structural characterization results show that sodium fluoride is highly dispersed in the catalyst and does not aggregate.

[0019] 2) The sodium fluoride used in this invention is a commercially available material that has not undergone any processing after purchase. The preparation method is simple and does not require complex and expensive instruments and equipment. It achieves a significant performance improvement at low cost. The prepared catalyst has high ammonia synthesis activity at low temperature and low pressure, which is beneficial for industrial application and provides a new idea for designing novel ammonia synthesis catalysts. Attached Figure Description

[0020] Figure 1 This is a flowchart illustrating the preparation process of a sodium fluoride-promoted ruthenium-based ammonia synthesis catalyst according to the present invention.

[0021] Figure 2 This is a comparison diagram of the ammonia synthesis activity of the catalysts prepared in Example 1 and Comparative Examples 1, 2, 3, and 4 of this invention.

[0022] Figure 3 This is a graph showing the activity and stability test results of the 5% Ru-1NaF / MgO catalyst prepared in Example 1 of this invention.

[0023] Figure 4 The X-ray diffraction patterns of the 5% Ru-1NaF / MgO catalyst before and after reduction and the unreduced Ru / MgO catalyst prepared in Example 1 of this invention are shown.

[0024] Figure 5 Scanning electron microscope and elemental distribution diagram of the 5% Ru-1NaF / MgO catalyst prepared in Example 1 of this invention. Detailed Implementation

[0025] To make the technical solution and advantages of the present invention clearer, the present invention and its beneficial effects will be described in further detail below with reference to specific embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.

[0026] Example 1

[0027] A method for preparing a sodium fluoride-promoted ruthenium-based ammonia synthesis catalyst includes the following steps:

[0028] S1. First, add 3.6g of magnesium oxide and 0.2g of sodium hydroxide to a beaker containing 120mL of deionized water and disperse thoroughly with stirring. Then, dissolve 0.36g of ruthenium trichloride in 20mL of deionized water and slowly add it dropwise to the beaker. After thorough stirring, transfer the mixture to a hydrothermal reactor for a hydrothermal reaction. The temperature of the drying oven used for the hydrothermal reaction was set to 160℃, and the reaction time was 24h. Afterward, obtain the solid product by centrifugation at a speed of 10000 r·min. -1 The solid was washed repeatedly with deionized water for 1 minute and centrifuged 2-3 times. It was then dried in a 100°C oven for 12 hours. Finally, the dried solid was calcined in an air furnace at 500°C for 3 hours at a heating rate of 2°C / min. -1 A ruthenium precursor / magnesium oxide composite material was obtained.

[0029] S2. Dissolve 4.2 mg of sodium fluoride in a flask containing 5 mL of deionized water, add 0.2 g of ruthenium precursor / magnesium oxide composite material, and impregnate for 12 h in an oil bath at 60 °C with stirring, keeping the flask sealed with a stopper during the process.

[0030] S3. Open the bottle stopper and continue stirring for 12 hours under oil bath heating at 60℃ to evaporate the moisture. Then dry in a forced-air drying oven for 12 hours at a temperature of 100℃.

[0031] S4. The dried product was reduced in a tube furnace with a flowing nitrogen-hydrogen mixture (N2 and H2 volume ratio of 1:3) at a temperature of 400℃ for 3 hours at a heating rate of 2℃·min. -1 To obtain a sodium fluoride-promoted Ru / MgO catalyst

[0032] The catalyst obtained in Example 1 was labeled as 5% Ru-1NaF / MgO.

[0033] Comparative Example 1

[0034] Sodium fluoride was used as a catalyst without any treatment to test its activity in the ammonia synthesis reaction.

[0035] The catalyst obtained in Comparative Example 1 was labeled as NaF.

[0036] Comparative Example 2

[0037] The specific steps for preparing the Ru / MgO catalyst alone, without adding sodium fluoride, are as follows:

[0038] The ruthenium precursor / magnesium oxide composite material obtained in step S1 was reduced in a tubular furnace with a flowing nitrogen-hydrogen mixture. The reduction temperature was set at 400℃, the reduction time was 3 h, and the heating rate was 2℃·min. -1 The catalyst was obtained.

[0039] The catalyst obtained in Comparative Example 2 was labeled as 5% Ru / MgO.

[0040] Comparative Example 3

[0041] The solvent used in the impregnation method is changed from water to tetrahydrofuran. The specific steps are as follows:

[0042] Dissolve 4.2 mg of sodium fluoride in a flask containing 5 mL of tetrahydrofuran. Add 0.2 g of ruthenium precursor / magnesium oxide composite material and impregnate in an oil bath at 60 °C with stirring for 12 h, adding reflux to prevent the liquid from drying out. Remove the reflux and continue stirring in an oil bath at 60 °C for 12 h to evaporate the solvent. Then dry in a forced-air drying oven at 100 °C for 12 h.

[0043] The dried product was reduced in a tubular furnace with a flowing nitrogen-hydrogen mixture at a temperature of 400°C for 3 hours at a heating rate of 2°C / min. -1 The catalyst was obtained.

[0044] The catalyst obtained in Comparative Example 3 was labeled as 5% Ru-1NaF / MgO-THF.

[0045] Comparative Example 4

[0046] The Ru / MgO was physically mixed with sodium fluoride using a grinding method, and this mixture was used as a catalyst. The specific steps are as follows:

[0047] Mix 0.2g of ruthenium precursor / magnesium oxide composite material and 4.2mg of sodium fluoride together in an agate mortar and grind manually for 15 minutes.

[0048] The above product was reduced in a tubular furnace with a flowing nitrogen-hydrogen mixture. The reduction temperature was set at 400°C, the reduction time was 3 hours, and the heating rate was 2°C / min. -1 The catalyst was obtained.

[0049] The catalyst obtained in Comparative Example 4 was labeled as 5% Ru / MgO + 1NaF.

[0050] Specific Application Example 1

[0051] The performance of the above catalysts was evaluated using a fixed-bed reactor.

[0052] First, the powdered catalyst is compressed into tablets using a tablet press, then crushed and sieved into particles of 20–40 mesh. 0.1 g of catalyst is weighed and mixed with silica sand of the same mesh size (catalyst to silica sand mass ratio of 1:10). This step is to overcome the potential external diffusion effect of the catalyst and to prevent catalyst powder from clogging the pipeline.

[0053] Subsequently, the catalyst bed is raised to the isothermal heating zone of the reaction tube using quartz tubes and quartz sand. After the catalyst is loaded, a layer of quartz sand must be added to the top of the bed to prevent the catalyst from being blown away by the airflow. Before starting the test, the airtightness of the device needs to be checked.

[0054] Then, high-purity N2 and H2 cylinders were used to supply synthesis gas, and the flow rates of the two gases were adjusted to maintain the space velocity at 36000 mL g / L at a flow ratio of 1:3. -1 h -1 By testing the concentration of ammonia in the outlet exhaust gas under set temperature and pressure, the ammonia synthesis reaction rate of the catalyst can be determined.

[0055] Finally, the concentration of ammonia in the outlet exhaust gas was obtained using chemical absorption. Prepare a 5 mmol / L solution. -1 A dilute sulfuric acid solution was used as the absorbent. During the test, the exhaust gas was passed into a known volume of acid solution, and stirring was applied to ensure complete absorption. After a period of time, the NH4+ in the absorbent was determined using ion chromatography (Qingdao Shenghan, CIC-D100). + The concentration of is converted into the ammonia synthesis reaction rate, as shown in the following formula:

[0056]

[0057] Where: C NH4 + NH4 in the absorption liquid + Concentration (mg / L) -1 );

[0058] V 酸 This represents the volume (L) of dilute sulfuric acid.

[0059] M is NH4 + molar mass (g mol) -1 );

[0060] m is the mass of the catalyst (g);

[0061] t is the absorption time (h);

[0062] r is the rate of ammonia synthesis (μmol g) -1 h -1 ).

[0063] The catalysts prepared in Example 1 and Comparative Examples 1, 2, 3, and 4 were subjected to activity evaluation and compositional characterization according to the specific application example 1. The experimental results are shown in [Figure 1]. Figures 2-5 .from Figures 2-5 As can be seen, the catalyst prepared by this invention has high ammonia synthesis activity and thermal stability at low temperature and low pressure. The added sodium fluoride is uniformly distributed on the catalyst, which has a significant effect on promoting the activity.

[0064] This invention provides a method for adding trace amounts of sodium fluoride as a promoter to a Ru / MgO catalyst via aqueous phase impregnation, thereby enabling it to withstand conditions at 400°C, 0.1 MPa, and 36000 mL g. -1 h -1 The reactivity at space velocity increased 10-fold to 2050 μmolg. -1 h -1 The catalyst remained highly stable even after 50 hours of reaction, indicating its high thermal stability. Compositional and structural characterization results showed that sodium fluoride was highly dispersed in the catalyst without aggregation.

[0065] Based on the disclosure and teachings of the foregoing specification, those skilled in the art can make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments described above, and any obvious improvements, substitutions, or modifications made by those skilled in the art based on the present invention are within the scope of protection of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.

Claims

1. A method for preparing a sodium fluoride-promoted ruthenium-based ammonia synthesis catalyst, characterized in that, The process includes the following steps: mixing sodium fluoride solution and ruthenium precursor / magnesium oxide composite material evenly, with a molar ratio of sodium fluoride to ruthenium of 1:1 to 2:1; stirring and impregnating at 50 to 70°C for 10 to 15 hours; evaporating the liquid to dryness; drying at 80 to 100°C for 12 to 24 hours; and finally calcining the dried product at 350 to 450°C for 2 to 4 hours under a reducing atmosphere to obtain a sodium fluoride-promoted Ru / MgO catalyst.

2. The preparation method according to claim 1, characterized in that, The preparation method of the ruthenium precursor / magnesium oxide composite material is as follows: an aqueous solution of ruthenium precursor is added dropwise to deionized water containing magnesium oxide and sodium hydroxide and subjected to a hydrothermal reaction at 150-170°C for 22-26 hours. After centrifugation, washing, and drying at 80-100°C for 12-24 hours, a solid product is obtained. The solid product is then calcined in air at 400-600°C for 2-4 hours to obtain the ruthenium precursor / magnesium oxide composite material.

3. The preparation method according to claim 2, characterized in that, The ruthenium precursor is ruthenium trichloride, ruthenium nitrite, or ruthenium acetate.

4. The preparation method according to claim 2, characterized in that, The molar ratio of ruthenium precursor to magnesium oxide to sodium hydroxide is 0.34–0.40:17–20:1–1.

1.

5. The preparation method according to claim 1, characterized in that, The sodium fluoride solution is an aqueous solution of sodium fluoride with a mass percentage of 0.08–0.18 wt%.

6. The preparation method according to claim 1, characterized in that, The evaporation time is 10-15 hours.

7. The preparation method according to claim 1, characterized in that, The reducing atmosphere is hydrogen, or a nitrogen-hydrogen mixture, wherein the volume ratio of N2 to H2 is 1:3, or a hydrogen-argon mixture.

8. The sodium fluoride-promoted ruthenium-based ammonia synthesis catalyst obtained by the preparation method according to any one of claims 1-7.

9. The application of the catalyst according to claim 8 in the field of thermocatalytic ammonia synthesis.